Brucella abortus Induces Collagen Deposition and MMP-9 Down-Modulation in Hepatic Stellate Cells via TGF-b1 Production - Arriola Benitez, Paula Constanza (2013)
In patients with active brucellosis, the liver is frequently affected by histopathologic lesions, such as granulomas, inflammatory infiltrations, and parenchymal necrosis. Herein, we examine some potential mechanisms of liver damage in brucellosis. We demonstrate that Brucella abortus infection inhibits matrix metalloproteinase-9 (MMP-9) secretion and induces collagen deposition and tissue inhibitor of matrix metalloproteinase-1 secretion induced by hepatic stellate cells (LX-2). These phenomena depend on transforming growth factor-β1 induction. In contrast, supernatants from B. abortus-infected hepatocytes and monocytes induce MMP-9 secretion and inhibit collagen deposition in hepatic stellate cells. Yet, if LX-2 cells are infected with B. abortus, the capacity of supernatants from B. abortus-infected hepatocytes and monocytes to induce MMP-9 secretion and inhibit collagen deposition is abrogated. These results indicate that depending on the balance between interacting cells and cytokines of the surrounding milieu, the response of LX-2 cells could be turned into an inflammatory or fibrogenic phenotype. Livers from mice infected with B. abortus displayed a fibrogenic phenotype with patches of collagen deposition and transforming growth factor-β1 induction. This study provides potential mechanisms of liver immune response induced by B. abortus-infected hepatic stellate cells. In addition, these results demonstrate that the cross talk of these cells with hepatocytes and macrophages implements a series of interactions that may contribute to explaining some of mechanisms of liver damage observed in human brucellosis.